Peningkatan Nilai Ekonomi Kotoran Kambing di Desa Sanankerto melalui Pembentukan Kelompok Tani - Arnanda Ajisaputra; Nurtjahja Juniarsa; Dias Agustin Dwi Jayanti; Helmi Sambora; Anang Lastriyanto (Universitas Nurul Jadid, 2024)
Sanankerto Village has an abundant number of livestock (goats), resulting in a significant accumulation of goat manure, which poses a potential health threat to the residents. To enhance the economic value of goat manure in Sanankerto Village, it is necessary to establish an institution focused on managing goat manure waste from upstream to downstream, namely a farmers' group. This community service program aims to initiate the formation of the Sanankerto Village Farmers' Group, with a focus on organizational quality systems, including vision, mission, objectives, quality policies, organizational structure, task mapping, SOPs, and work instructions (IK). Using the PRA (Participatory Rural Appraisal) method, an agreement was reached between the program implementers and Sanankerto Village officials to establish the farmers' group. Due to time constraints, the reported program for forming the farmers' group covers only the formulation of the vision, mission, objectives, and quality policies. This program successfully formulated the vision, mission, and quality policies of the farming group, although further action is still required for full implementation. Based on the achievements to date, it can be concluded that the establishment of the farming group using the PRA method has successfully raised community awareness of the economic potential of goat manure